Design and Fabrication of A trapezoidal Form for Precasting of Concrete Canal-lets - Ahmed, Tahir Mohammed (International Journal of Environment, Agriculture and Biotechnology, 2022)
Canalization system at Rawakeeb Research Station (RRS) experienced high water losses due to seepage. Based on maximum expected discharge at RRS of 200 m3/s, a trapezoidal cross section form is designed then fabricated of local materials (angle bars, rectangular pipes, steel sheets, iron steel shaft, roller thrust bearings, steel wire and nuts) with the dimensions of 82 cm (width) x 2.5 m (height) x 82 cm (long) to precast concrete canal-lets of 1 m × 55 cm × 8 cm (length, width, thickness) as required for lining of RRS canal. Designed unit discharge and flow velocity were found to be 0.06 m3/s, 0.5 m/s, precasted concrete canal-lets then cured for 14 days. The suggested trapezoidal form design can be adopted to produce trapezoidal precasted concrete canal-lets without distortions, precasted concrete canal-lets provided required water tightness. As a result the suggested precasting technique can be adopted.